Use of Ligand-Free Iron/Copper Cocatalyst for Nitrogen and Sulfur Cross-Coupling Reaction with 6-Iodoimidazo[1,2-a]pyridine - Tber, Zahira; Hiebel, Marie-Aude; Akssira, Mohamed; Guillaumet, Gérald; Berteina-Raboin, Sabine (Synthesis, 2015)
A ligand-free cooperative bimetallic iron/copper catalysis system was found to introduce various azoles and thiols onto 6-iodoimidazo[1,2-a] pyridine. After optimization, the inexpensive, nontoxic, air-stable, and commercially available CuO and FeCl2·4H2O enabled a regioselective N- and S-arylation of common nitrogen heterocycles and of a broad range of mercaptans including aliphatic, aromatic, and heterocyclic thiols.
Keywords: iron; copper; bimetallic catalysis; imidazo[1,2-a]pyridine; N and S cross-coupling